Capacity-Based Evaluation Of Retrofitted Residential Buildings: Integrating Damage Assessment And Maintenance Management - Bhalerao, Sfoorti Dattu; R. Patil, Ashwini; Sawant, Sneha (Journal of Neonatal Surgery, 2025)
This study presents a capacity-based evaluation framework for retrofitted residential buildings, focusing on integrating damage assessment and maintenance management to enhance structural integrity and longevity. As buildings age, structural integrity is often compromised by environmental exposure and design limitations, necessitating retrofitting to improve resilience against seismic and environmental stressors. However, the effectiveness of retrofitting is largely determined by post-retrofit maintenance practices. This research aims to bridge the gap between retrofitting implementation and sustained building performance through a structured methodology that combines damage assessment with proactive maintenance strategies. The study employs a mixed-methods approach, utilizing quantitative surveys and qualitative case studies to analyze real-world retrofitted buildings. The results highlight key correlations between retrofit types, damage severity, and maintenance costs, demonstrating that more severe damage typically requires higher retrofit levels and leads to increased maintenance costs. Additionally, the research advocates for predictive maintenance techniques to identify potential issues early, reducing long-term repair costs and extending the lifespan of retrofitted buildings. This research provides valuable insights for property owners, engineers, and policymakers to optimize building maintenance and retrofit practices, ensuring cost-effective management and enhanced building resilience.